Role of Powder Properties and Flowability in Polymer Selective Laser Sintering—A Review - Xi Guo; Brij M. Moudgil (KONA Powder and Particle Journal, 2023)
Polymer selective laser sintering (SLS) is an additive manufacturing technology that involves the melting of a selected area of particles on the powder bed. A 3D component is then printed using layer-by-layer sintering of the powder bed. SLS is considered one of the most promising technologies applicable to a variety of applications, particularly for manufacturing customized design products with high geometric complexity, such as patient-specific designed implants, surgical tools. Currently, only a small number of polymers are available that are suitable for SLS due to the complex multiple physical phenomena involved. Therefore, it is critical to develop new materials in order to fully realize the potential of SLS technology for manufacturing value-added customized products. For a given material, the quality of powder spreading in SLS plays a key role in printing performance and is a precondition for new material development. The aim of this review is to (1) present flowability characterization methods suitable for SLS, (2) examine the influence of powder properties and flowability on laser–material interaction and the quality of the final part, and (3) discuss the methods adopted in the literature to improve the quality of powder spreading.